Synthesis and Characterization of Mercuric Sulfide Nanoparticles Thin Films by Pulsed Laser Ablation (PLA) in Distilled Water (DW) - N. Mohammed; H. f. Dagher (Iranian Journal of Materials Science and Engineering, 2020)
Thin films of meta-cinnabar mercuric sulfide (β-HgS) nanoparticles (NPs) was prepared by pulsed laser ablation (PLA) utilizing a pellet of cinnabar mercuric sulfide (α-HgS) was immersed in distilled water (DW). Q-switched Nd:YAG laser of 1064 nm wavelengths with repetition rate (1hz) and fluency (1.5 J/cm2) applied for ablation. Structural, morphological and particle sizes of the β-HgS NPs are invastigated by analyzing XRD, AFM, SEM and TEM measurements. Their crystal structure is transformed from hexagonal (wurtzite) of the α-HgS target material to cubic (zinc blende) β-HgS NPs. The optical properties of the β-HgS NPs are measured by UV–visible spectrophotometer. The direct band gap is calculated to be (2.45eV) of small particles (4-6.2nm) moreover, the band gap value of smallest particles (1-4nm) is (3.47eV) according to the optical transmission spectra